The Correlation of High-Risk Age on Women of Reproductive Age and Post Partum Bleeding Case - Laily Prima Monica; Ulfa Husnul Fata (Journal of Ners and Midwifery, 2022)
During the post partum there are physiological changes such as uterine involution and lochia expenditure. Excess lochea discharge to more than 500 cc after delivery is called postpartum hemorrhage. The purpose of this study was to analyze the correlation of high-risk age and the incidence of postpartum hemorrhage in the maternity room of Syuhada Haji Hospital, Blitar City. The type of the study was analytic with a cross sectional approach. The population was all postpartum mothers who gave birth in the maternity room of Syuhada Haji Hospital, Blitar City on January â€“ December 2018. The poplation was 672 respondents and the sample was 97. The sample was taken systematically by random sampling. The measuring instrument used documentation guidelines. The study was carried out by Chi-Square test. It was obtained that X2 count (0.00) was less than Ã¡ (0.05), then H0 was rejected and H1 was accepted. In conclusion there was a correlation between highrisk age and postpartum hemorrhage incidence. It is expected that the research area will pay more attention in the handling and care of pregnant women of reproductive age so that at the age that is slightly at risk for the occurrence of postpartum hemorrhage, they will not experience postpartum hemorrhage. And women of high-risk age should be able to give birth at hospital in order to reduce complications.